Improving the Management of Islamic Study Group: A Case Study of Jammiyatul Ummahat Majelis Ta lim in Special Capital Region of Jakarta - A, Nuraeni, H.; A, Arif; N, Bariyah, O. (Asian Journal of Contemporary Education, 2019)
This study aims to improve the management of Islamic Study Group (Majelis Ta’lim) in Special Capital Region of Jakarta (DKI Jakarta). The research employed qualitative research with a case study approach. The study was conducted at Jamiyyatul Ummahat Majelis Ta’lim(the name of Islamic Study Group) and four people participated in this study, namely 1) head of the majelis ta’lim, 2) staff of the majelis ta’lim, 3) the teacher, 4) the member. Data collection involved observation, interview, documentation, and triangulation. Data were analyzed using Miles & Huberman’s Interactive Model. The results of the study showed that the management of the Jamiyyatul Ummahat Majelis (the name of Islamic Study Group had been developed in terms of its modernization in the learning management, improvement of human resources, as well as the management of financial systems and infrastructures. It also focused itself on the level of quality achievement gradually and sustainably. The results also underline that the modernization occurred because of several factors, including the management function in the administration of the majelis ta’lim and the educational level improvement of human resources. The leaders and administrators of majelis ta’lim were elementary school graduates, but now 75% of them hold an undergraduate degree. Thus, the improvement of education leads to better and more modern management.